APLIKASI SENSOR MOISTURE PADA KAYU DI ROTRA FURNITUR TAHUNAN JEPARA - Susila, Dwi Agus; Mohammad, Gunawan; Fitrianto, Muhammad Ilham Adji; Said, Aminudin (Institut Seni Indonesia Padang Panjang, 2023)
The drying oven is a primary support in the furniture manufacturing business, which is carried out using simple and natural techniques, namely the use of solar heat. Based on findings at the partner's location, this collaborative research between lecturers and students will focus on wood drying as the main issue with the aim of helping to increase the potential benefits of wood dryness at Rotra Furniture Annual Jepara in order to maximize furniture production. This research is related to the Product Design Study Program roadmap through the development of education, culture, and creative industry that will be implemented at Rotra Furniture, especially in relation to the use of wood raw materials with a national standard dryness level of 12%, which is suitable for the needs of furniture design that is now developing again. The target of this research is to investigate and report the basic principles of the technology for installing moisture sensor devices with the recommended technological concept, targeting TKT at level 1 within one year. This research will continue to TKT targets at levels 2 and 3 with the readiness for implementation and proof of concept of technology on wood furniture business operators directly. The methodology used is experimental to collect performance data based on time and the rate of drying in the wood oven. The experiment was carried out using local teak wood that was wet after sawing division until it reached a level of dryness that was ready to become furniture production material. This study also involves data collection techniques with field study approaches through direct surveys in the field and interviews with the owners of the Rotra Furniture business. The data analysis technique used in this research is an interactive model, including data collection, data reduction, data analysis, and conclusion drawing. This research has been carried out up to 70% of activities and will be continued with further research with the support of various competent parties.